Pengelolaan Wakaf Modern dalam Perspektif Maqashid Syariah - Sofuan (Journal of Islamic Economic and Law (JIEL), 2025)
Modern waqf management is an effort to optimize the utilization of waqf assets through management and business approaches in order to achieve public benefit (maslahah) and avoid harm (mafsadah) for the welfare of society. This system emphasizes a more administrative and structural governance and is directly supervised by the government through the Indonesian Waqf Board (BWI) based on Law Number 14 of 2014 concerning Waqf. The essential elements of modern waqf include the subject of the contract, the object of the contract (mauquf bih), shighat (ijab qabul), and the waqf institution as the managing body. From the perspective of maqashid shariah, modern waqf management is understood as an effort to draw closer to Allah Swt. by dedicating a portion of wealth in an institutionalized manner, thereby providing optimal and sustainable social and humanitarian benefits in accordance with the principles of maqashid shariah.